Strategi Guru Musik Dalam Meningkatkan Kompetensi Siswa Melalui Pemanfaatan Aplikasi Moises Ai Dalam Latihan Musik Band - Asep Rizwan Nurfalah; Yudi Sukmayadi; Ayo Sunaryo (Global Action and Education for Society, 2025)
Band music learning at SMAN 8 Bandung often faces obstacles, such as limited rehearsal time, difficulty understanding song structures, lack of appropriate backing tracks and lack of rhythmic accuracy and coordination between band members. Music teachers need innovative strategies to overcome these challenges and improve students' competence in playing music. One solution that can be applied is the utilization of the Moises AI application, which allows for more flexible and interactive instrument separation, tempo setting, and rehearsal. This study aims to analyze music teachers' strategies in utilizing Moises AI to improve students' competence in band music practice. The method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results showed that the use of Moises AI helped students more easily understand song structures, improve rhythm accuracy, and develop creativity and improvisation in music playing. In addition, the strategies applied by teachers include exploration of AI features, project-based exercises, and collaborative approaches to learning. With the right strategies, Moises AI becomes an effective tool in enhancing students' learning experience. Therefore, music teachers are advised to more actively integrate AI technology to create innovative, interactive and effective music learning.